Entrepreneurial Ability, Market Selection and Setting Up an Infant Industry-Theory and Evidence from the Japanese Cotton Textile Industry - Atsushi Ohyama; Serguey Braguinsky; Kevin M. Murphy (The University of Chicago, Center for the Study of the Economy and the State, 2001)
In this paper we develop a new insight into the infant industry argument for protection, in the setting where entrepreneurs are differentiated by talent. The speed of technological progress depends on the quality of ideas and the incentives to innovate, not on the scale of the industry, and unprotected open economy competitive regime furnishes the best environment for innovation- led industrial growth even in the presence of industry-wide increasing returns to scale. Competitive market selection of ablest entrepreneurs forms a crucial condition for successful industrialization. The model is tested against the evidence of industrial revolution in Japan that presents a unique historic experiment in which an internationally competitive textile industry was eventually set up without government protection after earlier experiments with subsidized firms had failed.
Keywords: 330